The effectiveness of the Halliwick concept hydrotherapy and Bobath (Neurodevelopmental Treatment-NDT) in the treatment of children with cerebral palsy–A randomised controlled trial - Konstantinos Chandolias; Eleni Argyroula Tsounia; Nikolaos Strimpakos; Efthalia Zogka; Thomas Besios; Georgios Marios Kyriakatis; Panagiotis Tsimeas; Athanasios Tsiokanos (Brain Disorders)
Background: Children with cerebral palsy (CP) often face challenges in motor function, balance, and daily activities. While land-based therapies such as the Bobath concept are widely used, complementary water-based therapies, including the Halliwick concept, offer unique opportunities to enhance rehabilitation outcomes. Objective: This study aimed to evaluate the effectiveness of Halliwick concept hydrotherapy on gross motor function, balance, speed, and daily life skills in children with CP. A secondary objective was to compare the combined intervention of Halliwick hydrotherapy and Bobath therapy (NDT) with Bobath therapy (NDT)alone. Methods: A total of 80 children with CP (mean age: 7.53 years) participated in this 9-month long randomised controlled trial. Participants were divided into three groups: the intervention group (n = 40), which received one session per week of both Halliwick hydrotherapy and Bobath therapy; control group 1 (n = 35), which received two sessions of Bobath therapy (NDT)per week; and control group 2 (n = 5), which did not receive any intervention. Two-way repeated measures ANOVA was conducted to compare the GMFM, PEDI, PBS, and TUG between time and groups, while a paired t-test to assess water-based (WOTA 1 & 2, SWIM, HAAR) through time. Results: Statistically significant improvements were observed in the intervention group when compared with control groups across all measures. The intervention group demonstrated greater gains in gross motor function, balance, daily activities, and speed, using the TUG test, compared to control group 1, with minimal changes observed in control group 2. Notable improvements included increased GMFM scores (6points improvement in the intervention group compared to 3.36 in control group 1(Wilks's Lambda = 0.807, F = 9.222, partial η2 = 0.193, p < 0.001)), balance (PBS: +3.8 points(Wilks's Lambda = 0.778, F = 11.002, partial η2 = 0.222, p < 0.001)), and daily activities (PEDI: +6.32 points(Wilks's Lambda = 0.849, F = 6.854, partial η2 = 0.151, p = 0.002)). Water-based assessments further highlighted substantial improvements in aquatic skills. Conclusion: Incorporating Halliwick hydrotherapy into rehabilitation programs for children with CP yields significant benefits, enhancing motor skills, balance, and daily functioning beyond what is achieved with land-based interventions alone. These findings highlight the importance of integrating complementary aquatic therapies into routine clinical practice for children with CP. Further research with larger, homogeneous samples and extended intervention durations is recommended to refine these therapeutic approaches.